Tinjauan Terhadap Tanah Warisan yang Dijadikan Agunan Peminjaman Uang Tanpa Sepengetahuan Ahli Waris (Studi Putusan Pengadilan Negeri Kisaran No.65/Pdt.G/2022/Pn.Kis) - Simanjuntak, Komis; Hayani, Masyita; Hutama Hutabarat, Dany Try (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Indonesian inheritance law is still pluralistic, meaning that it is governed by several legal systems, namely customary inheritance law, Islamic inheritance law and civil inheritance law. The formulation of various types of inheritance laws was due to the needs of the people at that time to respond to the various types of interests they faced, so that their legality was officially justified by the country's constitution for its application until now, without unification of laws. related to inheritance law, to fulfill the legal needs of the Indonesian people now and in the future in order to build a just and prosperous society based on Pancasila and the 1945 Constitution. This legal research uses empirical legal research, which gets references from primary legal materials, namely: Legislation, Judge's Decision. Secondary legal materials, namely: law books, and legal dictionaries. Tertiary legal materials, namely: Big Indonesian Dictionary. The plaintiff stated in the argument for his lawsuit that is posita (pundamentatum petendi) number 3, arguing that under the Plaintiff's rights were obtained from the late Nurhabibah who was married to Anuar with 6 sons and 1 daughter, the plaintiff should argue the plaintiff's civil ties with Sahbudin, Ilham, Herman, Syafaruddin , Muhammad Suheru, Lilinah (Defendant II) and withdrew as a Party in this case with the intention of clarifying the problem and distribution of inheritance (legacy), because the plaintiff could not dissolve the plaintiff's civil ties with 7 heirs and only revoked 1 part in this case and has not involving 5 disputing parties so that the lawsuit has a plurium litis consortium divide defect factor. The law of succession in the concept of civil law is one of the provisions that controls humans and humans in terms of inheritance (heritage). Not only that, the law of inheritance affects property if it is not finalized so that it will lead to disputes between the heirs.